Óbitos por doenças cardiovasculares entre idosos no município de Belém-Pa (1990-2005) - NASCIMENTO, Aline Marques (2023)
The objectives of this study were to analyze the most important causes of mortality from diseases of circulatory system, among elderly people living in the Belém municipality, from January 1990 through December 2005. A retrospective study, that analyzes cardiovascular diseases deaths in elderly people (60 or more years old), living in Belém-Pará was conduced, based on data drawn from the Mortality Information System (SIM). Data regarding populations were obtained from DATASUS. The variables was age, gender and death causes classified according to International Classification of Diseases Review 9ª and 10ª, for each year and grouped in four periods with four years. The principal cardiovascular death cause group among elderly people, in analyzed period, was cerebrovascular diseases, followed by ischemic heart disease. There was a decline in mortality rates, in all groups studied between the first and the last periods. The gender group with the largest proportion of deaths was the group of the old males and the group of the oldest elderly. The decline in mortality rates was most expressive in old females. That was decrease in difference between cerebrovascular diseases and ischemic heart diseases death rates, among women, which did not occur among the men. The results show a possible inversion trend between cerebrovascular diseases and ischemic heart diseases mortality rates among women. Moreover, in spit of the decline, the mortality by cardiovascular diseases stays being a important cause of obits among elderly people. Thus, is necessary adoption of health measures for elderly people that propitiates precocious identifications and treatment of these injuries just as prevention, with the aim of diminishing the expected number of fatal outcomes.